PENGARUH BRAND AWARENESS DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI PADA PENGGUNA SMARTPHONE IPHONE DI PT TELETAMA ARTHA MANDIRI) - Ni Nyoman Suarniki; Penta Lestarini Budiati; Rizki Amalia Afriana (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
The purpose of this study was to determine the effect of brand awareness and perceived quality on iPhone purchasing decisions. The type of research is quantitative research, the research population is all mobile phone users, the sample is determined by 100 respondents with a simple random sample technique, data collection using google form. And quantitative descriptive data analysis method, with the help of SPSS for windows. The results of this study indicate that the average total value of both male and female consumers regarding the level of Brand Awareness and Perceived Quality is high. Brand Awareness and Perceived Quality simultaneously affect purchasing decisions. While partially shows that Brand Awareness has an effect on purchasing decisions, Perceived Quality has no effect on purchasing decisions.